APPLICATION OF DIFFERENTIATED INSTRUCTIONS IN ENGLISH CLASSES - Nilufar Jamoliddinova (Western European Studies, 2024)
Teachers sometimes fail to give appropriate teaching instructions that are suitable for a mixed-ability classroom because these instructions do not match students’ needs, interests, and proficiency levels. The main purpose of the present study is determining the practicability of the “Differentiated Instruction” (DI) activities in school grades in Namangan, in accordance with the teachers’ perceptions, by considering important roles in the practice of the approach. Data for this study were collected using non-participant natural type of observation and unstructured interview with English language teachers (N=3) from the same school (School 7) in Namangan city. Observation and interview data revealed that teacher experience affect the way of utilizing DI strategy. Also it was identified that EFL teachers need a special trainings and workshops concerning the usage of DI effectively in teaching.
Keywords: differentiated instructions; grammar; RAFT; tiered activity